Integrating SANS and fluid-invasion methods to characterize pore structure of typical American shale oil reservoirs. Issue 1 (December 2017) - Zhao, Jianhua; Jin, Zhijun; Hu, Qinhong; Jin, Zhenkui; Barber, Troy.; Zhang, Yuxiang; Bleuel, Markus
Abstract An integration of small-angle neutron scattering (SANS), low-pressure N2 physisorption (LPNP), and mercury injection capillary pressure (MICP) methods was employed to study the pore structure of four oil shale samples from leading Niobrara, Wolfcamp, Bakken, and Utica Formations in USA. Porosity values obtained from SANS are higher than those from two fluid-invasion methods, due to the ability of neutrons to probe pore spaces inaccessible to N2 and mercury. However, SANS and LPNP methods exhibit a similar pore-size distribution, and both methods (in measuring total pore volume) show different results of porosity and pore-size distribution obtained from the MICP method (quantifying pore throats). Multi-scale (five pore-diameter intervals) inaccessible porosity to N2 was determined using SANS and LPNP data. Overall, a large value of inaccessible porosity occurs at pore diameters <10 nm, which we attribute to low connectivity of organic matter-hosted and clay-associated pores in these shales. While each method probes a unique aspect of complex pore structure of shale, the discrepancy between pore structure results from different methods is explained with respect to their difference in measurable ranges of pore diameter, pore space, pore type, sample size and associated pore connectivity, as well as theoretical base and interpretation.